Association between patellofemoral pain syndrome and hip morphology - Sanchez, Hugo Machado; Sanchez, Eliane Gouveia de Morais; Nascimento, Savana Brandão (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Patellofemoral pain syndrome (PFPS) is one of the most common conditions in the knee joint, there still unclear etiology. Objective: The objective of this study was to investigate the association of PFPS with the morphology of the hip. Method/Design: For this study were evaluated 41 university students aged between 18 and 30 years divided into group with PFPS and control group, in which we analyzed the distance from the anterior superior iliac spine (ASIS), length of the lower limbs (LL) away from the patella ASIS bilaterally, lateral bending and iliac slope. Results: After data collection and subsequent tabulation, it was found that the group with PFPS showed contralateral iliac increase the pain (p = 0.01), moreover, was also found to the side of prevalence of pain is the side not dominant (p = 0.00). Conclusions: It can be inferred that there is little relationship between the morphological changes of the hip with the PFPS, as only found a side tilt of the pelvis in volunteer group that reported a previous knee pain.